The role of mediator subunit MED7 in Arabidopsis development - Kumar, Koppolu Raja Rajesh; Blomberg, Jeanette; Björklund, Stefan (Frontiers in Plant Science, 2025)
MED7, a middle-module subunit of the transcriptional co-regulator Mediator complex, plays a critical role in gene regulation in Arabidopsis thaliana, where it is encoded by two paralogs, MED7A and MED7B. We present phenotypic analyses of homozygous MED7-silenced transgenic lines with significantly reduced expression of both MED7 paralogs under autotrophic conditions. Our findings demonstrate that MED7 is essential for proper cotyledon opening during de-etiolation, as the silenced lines showed a marked delay in this process. Additionally, these lines displayed distinct morphological alterations, including hyponastic cotyledons, elongated hypocotyls, and modified root architecture, such as shorter primary roots and impaired root hair development in light-grown seedlings. MED7 silencing also significantly hindered light-induced adventitious root (AR) formation on the hypocotyls of etiolated seedlings, leading to a notable reduction in AR production. Moreover, MED7 silencing impacted the timing of floral transition and shoot branching, resulting in delayed flowering and an increased number of primary cauline branches on the inflorescence stem. Together, these results underscore a central role for MED7 in orchestrating key developmental processes in plants.